2011
DOI: 10.1111/j.1537-2995.2011.03383.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and acceptance of public cord blood banking among practicing obstetricians in the United States

Abstract: Obstetricians are generally familiar with the utility of donated cord blood in transplantation, but could benefit from additional information regarding how cord blood is used in transplantation. Further, obstetricians play an important role in encouraging women to donate their baby's cord blood to a public CBB, are willing to do so, and indicate a desire for more information so they can effectively educate their patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 20 publications
(43 reference statements)
1
25
0
3
Order By: Relevance
“…Maternity staff members involved in perinatal care in this study were found to be adequately informed about UCB banking; a great majority of them knew conditions potentially treatable with UCB and knew the differences between private and public banks. These results are more encouraging than the results from a similar research conducted by Walker and colleagues, in which 49% of obstetricians indicated they had insufficient knowledge about UCB donation to effectively answer patients' questions (Walker et al, 2012). However, almost two-thirds of maternity staff members would like additional information about this topic and it is also important for family doctors to have knowledge about UCB as they can communicate this information to prospective parents.…”
Section: Dear Sirmentioning
confidence: 69%
“…Maternity staff members involved in perinatal care in this study were found to be adequately informed about UCB banking; a great majority of them knew conditions potentially treatable with UCB and knew the differences between private and public banks. These results are more encouraging than the results from a similar research conducted by Walker and colleagues, in which 49% of obstetricians indicated they had insufficient knowledge about UCB donation to effectively answer patients' questions (Walker et al, 2012). However, almost two-thirds of maternity staff members would like additional information about this topic and it is also important for family doctors to have knowledge about UCB as they can communicate this information to prospective parents.…”
Section: Dear Sirmentioning
confidence: 69%
“…Several participants emphasized the importance of buy‐in, whether they were referring to the willingness of prenatal care providers and labor and delivery staff to inform laboring women about donation or for physicians to take the time—for which they are not always reimbursed—to do a collection that meets volume criteria for banking. Staff that offer routine prenatal care in obstetricians' offices and labor and delivery staff in hospitals may feel they have too much to accomplish without the additional effort cord blood banking requires and may be reluctant to take the time to inform women about donation, but their efforts are critical 20,30 . As one participant noted:…”
Section: Resultsmentioning
confidence: 99%
“…For each subject, a maximum score of 58 could be calculated. The knowledge level score was categorized into 3 levels indicated by Poor knowledge (0-19), Moderate knowledge (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) and Good knowledge (39-58). Thus, the higher the score is the higher level of knowledge among health providers.…”
Section: Data Analysis and Scoring Measurementsmentioning
confidence: 99%